Originally Posted by

**danielle_54321** Simplifying Rational expressions.

4x + 4/ 3x-3 X 6x - 6/5x+5

the question askes to simplify by bringing both terms to lowest common terms before multiplying. The answer is supposed to be 8/5, where 1, -1 are not equal to zero.

I can't figure out how to obtain my result. Here is my rough work, could someone help me to figure out what I am doing wrong?

4x + 4/ 3x-3 X 6x - 6/5x+5

= 4x + 4/ 1-1 X 2-2/5x+5

=4x + 4/ 0 X 0/5x+5

= 0/0 = undefined. (we are supposed to "cross-cancel" by crossing out like terms and such)